2015
DOI: 10.1002/jat.3186
|View full text |Cite
|
Sign up to set email alerts
|

Sub‐chronic exposure to fluoride impacts the response to a subsequent nephrotoxic treatment with gentamicin

Abstract: Fluoride is an important groundwater contaminant, and more than 200 million people are exposed to high fluoride levels in drinking water, the major source of fluoride exposure. Exposure above 2 ppm of fluoride is associated with renal impairment in humans. In rats, moderate levels of fluoride induce kidney injury at early stages in which the glomerular filtration rate (GFR) is not altered. In the present study, we investigated if sub-nephrotoxic stimulus induced by fluoride might impact the response to a subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…Our results are consistent with these observations, showing increased HSP-27 and decreased HSP-70 in the kidneys after treatment with gentamicin. Cilastatin restored the levels of both HSPs, thus helping to mitigate the effect of gentamicin, as other authors have shown [ 35 ].…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Our results are consistent with these observations, showing increased HSP-27 and decreased HSP-70 in the kidneys after treatment with gentamicin. Cilastatin restored the levels of both HSPs, thus helping to mitigate the effect of gentamicin, as other authors have shown [ 35 ].…”
Section: Discussionsupporting
confidence: 64%
“…Indeed, there is a direct relationship between the presence of stress and activation/inhibition of HSPs [ 16 ] and in several models of nephrotoxicity, HSP-27 is overexpressed owing to its antioxidant and antiapoptotic role [ 33 ]. Likewise, HSP-70 has a reduced function when gentamicin specifically binds to it, which has been linked to increased renal toxicity [ 34 , 35 ]. Our results are consistent with these observations, showing increased HSP-27 and decreased HSP-70 in the kidneys after treatment with gentamicin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is evidence that accumulation of this element causes various adverse effects in human tissue (82). The kidney, as the main organ in excretion of F, undergoes toxicity by accumulation of renal tubular cells, resulting in oxidative stress and peroxidation of the cell membrane lipids (83,84). Fluoride induces various (82,84).…”
Section: Fluoridementioning
confidence: 99%
“…Thus, inhibition of megalin or Na+, K+-ATPase can lead to depletion of iodine stores and iodine deficiency. While there are no studies in literature examining the relationship between F exposure in humans and megalin expression, recently it has been found in animal models that chronic F exposure inhibits megalin expression [217]. It has been observed in animal studies that a decrease in megalin expression leads to a decrease in proximal tubule albumin (ALB) reabsorption [218], leading to enhanced urinary excretion.…”
Section: Molecular Mechanisms Of Fluoride Inhibition Of Iodine Hommentioning
confidence: 99%